Comparative studies on the electronic transport in magnetically quantized low band gap semiconductor system - Shrestha, S; Sarkar, C K (BIBECHANA, 2020)
The Q1D system formed by magnetically confined system is attracting attention of researchers in device application because it is capable of over-looking the various techniques of fabrication difficulties and defects created by such fabrication techniques. In the presence of a high magnetic field, the transverse component of the energy dispersion relation gets quantized into various equally spaced energy levels called Landau levels and the motion of the carriers is completely restricted. However, the longitudinal component along the field is still free to move. The mobility of such system is enhanced when a low effective mass semiconductors n-HgCdTe (Mercury Cadmium Telluride) is used. The band structure of n-HgCdTe is found to be nonparabolic due to its low band gap according to Kane [Phadke and Sharma, 1975]. Recent publications, based on experimental verifications of transport coefficient of n-HgCdTe of Chen and Sher [Chen and Sher, 1982] show that the band structure of Mercury Cadmium Telluride (MCT) is more hyperbolic in nature rather than nonparabolic. The author has compared the effect of band structures on the various transport properties of MCT such as mobility, Seebeck coefficient, thermal conductivity, figure of merit (Z) etc. The figure of merit is a very important property of a material to be used in thermoelectric devices, such as cooler, refrigerator etc. The product of Z and temperature i.e. (ZT), a dimensionless quantity is found to be maximum for parabolic band structure and is followed by nonparabolic and hyperbolic band structures for all ranges of variation of temperature as well as magnetic field. Taking the hyperbolic band structure of MCT, the effect of high and low temperature scattering mechanisms on ZT is also observed. BIBECHANA 17 (2020) 34-41